Intersecting Experiences: Class, Gender, Ethnicity and Race in the Lives of Highly Skilled Migrants in Finland - Kaisu Koskela (Nordic Journal of Migration Research, 2019)
The aim of this article is to study the experiences of highly skilled migrants from an intersectional perspective. Based on a case study of a group of skilled migrants in Finland, this article explores the interplay of various social identities and categorizations in their everyday life. I argue that although class markers are an important element in the self-defined group identification for skilled migrants, they are also subjected to intersecting social categorizations, stereotyping and assumptions based on gender, ethnicity, race and nationality, creating different experiences and belongings for different skilled migrants. Anthias’ concept of ‘translocational positionality’ is used to highlight how these intersections are highly situational, context specific and relative to other actors in the Finnish context.